THE ROLE OF THE LIMITED PARTNER DEEMING PROVISION IN THE INCOME TAX ACT: DOES SECTION 24H(2) ACHIEVE ITS INTENDED PURPOSE? - Afton Titus (Obiter, 2014)
The 1990s brought the announcement that National Treasury plans to rewrite the entire Income Tax Act 58 of 1962. The rationale for this ambitious endeavour was founded on the practical difficulties encountered with applying an Act that what was little more than a collection of ad hoc sections. Nothing further was said of this objective until 2005, when the Finance Minister confirmed that the rewrite remained a long-term goal, although he was uncertain when the process would begin. In 2010, it was stated that the rewrite of the Act would begin with the tax treatment of employment income. The potential rewrite of the Act is an opportune catalyst to investigate the continued usefulness or otherwise of section 24H(2), and the role it has assumed in the tax treatment of partnerships – particularly limited partnerships – in South African law. This paper questions whether South African law needs this particular provision. In doing so, I question whether the doubts that provided the impetus for the introduction of this section are sound, or whether the section only serves to raise more questions than it answers.